HPTLC METHOD DEVELOPMENT AND VALIDATION OF TRANDOLAPRIL IN BULK AND PHARMACEUTICAL DOSAGE FORMS - N. Sreekanth; Bahlul Z.Awen; Ch. Babu Rao (Wolters Kluwer Medknow Publications, 2010)
A simple, precise, accurate and rapid high performance thin layer chromatographic method has been developed and completely validated for the estimation of trandolapril in bulk and pharmaceutical dosage forms. Quantification of trandolapril was carried out with percolated silica gel 60F 254 as stationary phase using mobile phase consisting of Chloroform: Methanol: Acetic acid (8:1.5:0.5 v/v/v) and scanned in Absorbance/Reflectance mode at 212 nm using Camag TLC scanner 3 with WinCAT software. The Rf value of trandolapril was found to be 0.54 (±0.03). The proposed method has permitted the quantification of trandolapril over the linearity range of 25-150 ng/spot and its percentage recovery was found to 99.7%. The intra day and inter day precision were found to be 1.26% and 1.4%, respectively. The limit of detection and the limit of quantification were found to be 18 ng/spot and 54 ng/spot, respectively. The proposed method can be successfully applied for the estimation of drug content of different marketed formulations simultaneously on a single plate and provides a faster and cost effective quality control tool for routine analysis of trandolapril as bulk drug and in tablet dosage forms.